Disaster Vulnerability and Poverty Level Among Residents of Lagos State, Nigeria - Ogunleye, Oluwayemisi; Arohunsoro, Segun; Ibitoye, O.A (Amcolabora, 2023)
This paper considers the relationship between disaster vulnerability and poverty among some residents of Lagos state, Nigeria. A well – designed and structured questionnaire was administered to 200 respondents across selected locations to generate primary data. The data were analyzed in percentages and with Pearson correlation among some variables. The research established the most frequent disasters experienced within these localities which include: flooding, fire disasters, diseases epidemics, building collapse etc. It identified the most vulnerable to disasters as females, disabled, children, ethnic minorities, elderly, and the low income earners. It also ascertained that the reason for their vulnerability was traceable to their poverty level which is easily expressed in the type of job they do for living, lack of access to information, the type of houses and environment they live. Besides, that poverty also contributes to the vulnerability of people to the numerous disasters. The correlation of disease vulnerability and some of the variables indices of poverty showed positive correlation. It explained some of the main mechanisms, which made the poor in particular exposed and vulnerable to disaster losses. In particular, the long – term and indirect consequences of disasters especially on the poor were discussed, both in terms of economic losses and human capital losses. Consequently, the conclusion was reached that disaster vulnerability and poverty has some correlation